Adsorption equilibria of CFC-115 on activated charcoal - Park, HM; Moon, DJ (AMER CHEMICAL SOC, 2003)
Equilibrium studies on the adsorption of chloropentafluoroethane (CFC-115, CF3CF2Cl) on an activated charcoal were carried out between 298 K and 358 K. Results were fitted with mathematical models such as Langmuir, Freundlich, and BET equations. The temperature dependence of BET parameters and the isosteric enthalpy of adsorption in the CFC-115-charcoal system are estimated. Among the two parameter models, the BET isotherm for CFC-115 fits the experimental results within 7% over the entired relative pressure range. Especially, the BET isotherm showed the best results with less than 2% in the higher relative pressure range. The enthalpies of adsorption of CFC-115 are of the same order of magnitude as the enthalpy of condensation, 14.62 kJ.mol(-1).
Keywords: CHLOROFLUOROMETHANES; DESTRUCTION; OZONE